PERANCANGAN APLIKASI DATA IKLIM-71 DI STASIUN KLIMATOLOGI KLAS I PULAU BAAI – BENGKULU - Reno Supardi (UNIB Press, 2021)
Climatology Station Class I PulauBaai Bengkulu under the auspices of the Meteorology, Climatology and Geophysics which produce so many daily weather data are not computerized well. By this author wants to help the staff to facilitate the observation of the results of the data contained in Baai Island Climatology Station Bengkulu. Based on these reasons make the authors develop a design data applications FKlim-71 computerized to help resolve some of the problems that often occur. In making this application there are some required data is data such as temperature, rainfall data, the data of solar radiation, a special weather event data, the air pressure data, the data humidity, and wind data.Application design is intended for Climatology Station Class I Baai Island Bengkulu because there making this application done. This application uses Microsoft Visual Basic programming language and MySQL as the database.The test proved that the application program database applications Fklim-71 can facilitate the performance of observer Climatology Station Class I PulauBaai Bengkulu.